SYNERGETIC NATURE OF THE LINGUOCULTURAL CONTENT IN THE LINGUISTIC WORLDVIEW (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The article examines the synergetic nature of linguocultural content within the linguistic worldview and analyzes the interrelation between language and culture in the framework of anthropocentric and cognitive paradigms. The aim of the study is to identify the synergetic organization of cultural information expressed through linguistic units, as well as to reveal the cognitive and communicative functions of linguoculturemes in the formation of a national worldview. The relevance of the article is determined by the need to conceptualize the cultural and cognitive function of language and its role in spiritual and social development under the conditions of the renewal of national consciousness in contemporary Kazakh society. In addition, the relevance of the study is reinforced by the necessity of considering the unity of language and culture on the basis of an anthropocentric paradigm. The research employed a comprehensive set of methods, including descriptive, linguocultural, cognitive, synergetic, semantic, etymological, contextual, and comparative-associative analysis. These methods enabled a systematic examination of the semantic structure of linguistic units, their historical and cultural foundations, and their functioning in literary texts. The theoretical significance of the study lies in its interpretation of the interaction between language and culture as a synergetic system, as well as in the deepening of the understanding of the conceptual nature of linguocultural units and their role in the formation of the linguistic worldview. The work contributes to the development of theoretical foundations in cognitive linguistics, linguoculturology, and the synergetic approach in linguistics. The practical significance of the study is determined by its applicability to the linguocultural analysis of literary texts, folklore, and historical-cultural materials, as well as to language teaching, the promotion of national culture, and the field of humanities education.